Clinicopathological spectrum of biopsy-proven renal diseases of patients at a single center in Sri Lanka: a cross sectional retrospective review - Chanaka Muthukuda; Vindika Suriyakumara; Cherine Sosai; Thilina Samarathunga; Maithili Laxman; Arjuna Marasinghe (BMC Nephrology, 2023)
Abstract Background The clinical presentation of renal diseases can vary widely. The lack of a comprehensive national registry for Sri Lanka makes it difficult to provide a detailed record of the various clinical presentations and histopathology of renal disorders in the nation. Therefore, this study aims to provide a record of the spectrum of renal diseases in Sri Lanka. Methods Renal biopsies performed at the nephrology unit in Colombo South Teaching Hospital (CSTH), Sri Lanka from March 2018 to October 2019 was retrospectively studied. Indications for renal biopsy were nephrotic range proteinuria, sub nephrotic range proteinuria, acute kidney injury without obvious etiology, chronic renal disease without obvious etiology and haematuria. Results A total of 140 native kidney biopsies were analyzed in which majority were females (55.7%). The mean age of the population was 46 ± 15.3 years. The most common indications for renal biopsy were nephrotic range proteinuria (54.3%), followed by sub-nephrotic range proteinuria (14.3%), nephrotic range proteinuria with haematuria (14.3%), sub-nephrotic range proteinuria with haematuria (9.3%), AKI without known cause (4.3%), and CKD without known cause (3.6%). The leading histopathological diagnoses were FSGS (22.1%), lupus nephritis (20%), PSGN (17.1%), DN (12.1%), HTN (9.3%), MCD (6.4%), IgA nephropathy (5.7%), IN (4.3%), vasculitis (2.1%), and MGN (0.7%). Conclusions The most common indication for renal biopsy was nephrotic range proteinuria in our population. FSGS was the most prevalent histopathological diagnosis and the least frequent diagnosis reported was MGN. The spectrum of renal diseases could differ according to the study location and it changes over time. Therefore, a renal biopsy registry is needed for documenting the changing disease pattern in Sri Lanka.